Optimalisasi desain kaki jack stand kapasitas 3 ton untuk stabilitas fungsi berbasis FEM Simulation - Febriyanto Febriyanto; Robi Sabara; Lukman Priyatna; Muhammad Ramadhan (Sultra Journal of Mechanical Engineering, 2026)
This study aims to optimize the leg design of a 3-ton capacity jack stand to improve structural stability under non-ideal loading conditions using the Finite Element Method (FEM). Uneven working surfaces may cause unequal load distribution among the supporting legs, resulting in stress concentration, local deformation, and structural instability. The research was conducted through Finite Element Analysis (FEA) simulations using SolidWorks Simulation by comparing the original design with a modified design incorporating reinforcing gussets and additional base plates on the supporting legs. Simulations were performed using four steel materials, namely ASTM A36, AISI 1020, AISI 1045, and AISI 4130, under both flat and uneven surface conditions. The analyzed parameters included Von Mises stress, strain, displacement, and Factor of Safety (FOS). The simulation results showed that uneven surface conditions increased stress and deformation in all materials due to non-uniform load distribution. The modified design demonstrated better structural performance than the original design, particularly when using AISI 1045 material. Under uneven surface conditions, the modified design reduced the maximum stress from 288.4 MPa to 201.1 MPa (30.27%), reduced strain by 20.49%, reduced maximum displacement by 31.43%, and increased the Factor of Safety from 1.815 to 2.934, representing an improvement of 61.65%. The results indicate that the optimization of the jack stand leg design through the addition of gussets and reinforcing plates effectively enhances structural stability and safety. Furthermore, the FEM–FEA approach proved to be an effective tool for evaluating and developing safer, more stable, and more reliable jack stand designs for static loading applications.